Analisis Perilaku Hidup Bersih Dan sehat (PHBS) pada Petugas Kesehatan di Rumah Sakit Umum Daerah Salewangang Kabupaten Maros - Reza Aril Ahri; Burhanuddin; Nurmiati Muchlis (Journal of Muslim Community Health, 2021)
Background: Health promotion has a very relevant meaning and meaning. The definition of health promotion is the process of empowering or empowering the community to maintain, improve and protect their health through increasing awareness, willingness and ability, as well as developing a healthy environment.This study aims to analyze the clean and healthy life behavior of health workers at Salewangang Regional General Hospital, Maros Regency. Method: This study uses quantitative methods with a total sample of 100. Statistically, the level of knowledge allocated has a significant and positive effect on the clean and healthy life behavior of health workers at the Salewangang Regional General Hospital, Maros Regency. Results: The value of the regression coefficient is 0.274, -0.011 infrastructure, 0.042 attitude, 1.114 hospital policy. This shows that an increase in knowledge, infrastructure, attitudes, hospital policies by 1% will increase the behavior of clean living on average by 27.4%, meanwhile, infrastructure has no significant effect.